Towards a norm of compliance in recreational fisheries - Bova, Christopher S (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2019)
The activity of fishing can be traced back to prehistoric times. However, only in the last century has there been a focus on the management of fisheries. Fishery regulations are tools used by resource managers with the aim of protecting the long-term sustainability of fishery resources. Although there is an overwhelming amount of evidence demonstrating the decline of fisheries, non-compliance with these regulations by fishers continues to manifest, which can exacerbate the negative ecological impacts of fisheries. Popular methods towards the measurement of noncompliance in fisheries derived from previous human dimensions literature may be flawed. Theories on improving compliance behaviour have typically relied on theory, which has at times proved paradoxical. Addressing the issues of non-compliance within a fishery of interest requires measuring the levels of non-compliance within the fishery and determining the relevant sociopsychological drivers behind the non-compliant behaviour. The data collection methods used during these assessments are limited in human dimensions research and are often case and context specific, requiring researchers to identify which approach is most practical for the specific fishery of interest. By identifying relevant behavioural drivers of non-compliance, a more effective approach aimed at improving compliance can be tailored. The recreational marine-based shore fishery (MBSF) in South Africa is not impervious to noncomplaint behaviour. In fact, it has been estimated to have relatively high rates of non-compliance. This high level of non-compliance makes the South African MBSF a unique and optimal context in which to undertake research that aims to formulate a framework towards compliance assessments and that develops a suitable approach for improving compliance rates. Using surveys to obtain compliance data can provide a range of details about violators, however they are susceptible to social desirability bias (SDB). Choosing the best method for controlling SDB required an assessment of existing methods for doing so. In this first part of the study, only fishers who were covertly observed breaking the rules were surveyed, using one of three methods for reducing SDB, to ground-truth the responses. Ground-truthing was done to determine which method would be most effective for a large-scale study within the same fishery. Of the methods used, which include the direct questioning method (DQM), the random response technique (RRT) and the ballot box method (BBM), all contained some level of SDB. However, the BBM provided a significantly higher level of response accuracy (79.6% ± 11.9) than the DQM (46.5% ± 14.9) and the RRT (44.3% ± 12.5). Random-stratified roving creel compliance surveys that employed the BBM were then undertaken at various locations along South Africa's coastline to estimate current rates of non-compliance, and the face-to-face results were compared to results from an identical online survey to determine the suitability of online surveys as a replacement. The results indicated that online surveys only represent a subgroup of the fisher population within the MBSF, suggesting that face-to-face survey methods are required to obtain a more comprehensive sample and a more robust estimate of noncompliance. The results, based on 453 face-to-face surveys, showed a high level of overall self-reported noncompliance (48.3%) within the fishery. Responses to Likert scale survey questions on various aspects of the fishery, including angler motivations for fishing, were then modelled to test the relationship between the anglers' responses and their compliance behaviour. In the South African MBSF context, the most significant behavioural drivers behind non-compliance related to normative concepts. Specifically, the poor perceptions of management and value-based legitimacy as well as low levels of moral obligation to adhere to the regulations appeared to contribute most to the observed non-compliant behaviour. Angler motivations for fishing also played a significant role in determining the compliance behaviour of anglers, with those fishing for food being more likely to violate regulations. In most countries, regardless of economic context, interventions to improve recreational fishery compliance have been developed around the instrumental concept. However, these findings suggest that for recreational fisheries, managers would do well to evaluate the impact of normative concepts on compliance and to design interventions aimed at addressing these. In the case of the South African MBSF, interventions that address angler perceptions of legitimacy and aim to correct misperceptions about social norms of compliance may provide a more practical and cost- effective method for improving poor compliance behaviour.
Keywords: Fishing -- Management -- South Africa; Fishery law and legislation -- South Africa